Modeling heat transport processes in enhanced geothermal systems: A validation study from EGS Collab Experiment 1. (December 2021) - Wu, Hui; Fu, Pengcheng; Frone, Zachary; White, Mark D.; Ajo-Franklin, Jonathan B.; Morris, Joseph P.; Knox, Hunter A.; Schwering, Paul C.; Strickland, Christopher E.; Roberts, Benjamin Q.; Vermeul, Vince R.; Mattson, Earl D.; et al.
Highlights: Analyzed heat transport processes in an intermediate-scale EGS field experiment. Developed a high-fidelity model incorporating a well-constrained fracture network. Demonstrated the capability in modeling heat recovery from EGS reservoirs. Abstract: Heat recovery from an enhanced geothermal system (EGS) is a complex process involving heat transport in both fracture networks and rock formations. A comprehensive understanding of and the ability to model the underlying heat transport mechanisms is important for the success of EGS commercialization but remains challenging in practice due to the generally insufficient characterization of EGS reservoirs. In the present study, we analyze an extensively monitored intermediate-scale EGS field experiment performed in a well-characterized testbed. The high-resolution, high-quality measurements from the field experiment enable the development of a high-fidelity model incorporating a well-constrained fracture network. Based on the field experiment, we investigate the complex heat transport processes in an EGS-relevant environment and validate the capability of a numerical approach in simulating these inherently coupled heat transport processes. A series of numerical simulations were performed to study the effects of different heat transport mechanisms, including thermal convection with fracture flow, thermal conduction in rock formations, and the Joule-Thomson effect. The agreement of thermal responses between field measurements and simulation results indicates that our numerical approach can appropriately model the heat transport processes pertaining to heat recovery from EGS reservoirs.